The Importance of English in Tourism industry: Vocational High School Students' Perception - Aulia, Nawang Fadia Ismi; Musyarofah, Lailatul; Andayani, Endah Alamsari (Universitas Pahlawan Tuanku Tambusai, 2026)
English proficiency plays a crucial role in preparing vocational high school students for careers in the tourism sector. However, discrepancies still exist between classroom instruction and workplace demands. This study aims to explore students’ perceptions of the importance of English in the tourism industry and factors influencing these perceptions. Using a qualitative descriptive research design, data were collected through open ended questionnaires and semi interviews with twelfth grade students of the Tourism Department at SMK Airlangga. The data were analyzed through organizing, coding, categorizing, and interpreting emerging themes. The findings indicate that students generally perceive English as an essential skill for communicating with foreign tourists and supporting future employment in tourism related fields. Internal factors such as motivation and self confidence, along with external factors including school learning activities, contribute to shaping students’ perceptions. The study concludes that contextual and application-based English instruction is necessary to align vocational education with tourism workplace requirements.